2022
DOI: 10.1136/jech-2022-219252
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and population health: a political-economic research agenda

Abstract: There is more than 30 years of research on relationships between income inequality and population health. In this article, we propose a research agenda with five recommendations for future research to refine existing knowledge and examine new questions. First, we recommend that future research prioritise analyses with broader time horizons, exploring multiple temporal aspects of the relationship. Second, we recommend expanding research on the effect of public expenditures on the inequality–health relationship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although income inequality and social mobility have been separately associated with population health, no studies have investigated the joint association of income inequality and social mobility with deaths of despair, to our knowledge. Recent literature has proposed focusing on the interactions between income inequality, social mobility, and population health as an important research agenda . The literature has also suggested that linking income inequality to cause-specific mortality instead of all-cause mortality, particularly avoidable and preventable mortality, could provide significant implications for policy responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although income inequality and social mobility have been separately associated with population health, no studies have investigated the joint association of income inequality and social mobility with deaths of despair, to our knowledge. Recent literature has proposed focusing on the interactions between income inequality, social mobility, and population health as an important research agenda . The literature has also suggested that linking income inequality to cause-specific mortality instead of all-cause mortality, particularly avoidable and preventable mortality, could provide significant implications for policy responses .…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has proposed focusing on the interactions between income inequality, social mobility, and population health as an important research agenda. 37 The literature has also suggested that linking income inequality to cause-specific mortality instead of all-cause mortality, particularly avoidable and preventable mortality, could provide significant implications for policy responses. 37 We thus addressed this knowledge gap by examining the interaction between county-level income inequality and social mobility with deaths of despair (suicide, drug overdose, and alcoholic liver disease) among working-age Black, Hispanic, and White populations.…”
Section: Introductionmentioning
confidence: 99%